Exploring Latin: structures, functions, meaning - Pultrová, Lucie; Vaníková, Martina (De Gruyter, 2025)
This two-volume work contains a selection of papers first presented at the 22nd International Colloquium on Latin Linguistics, held in Prague (2023). The papers address important issues in Latin linguistics with a variety of theoretical and methodological approaches. The first volume ("Word") contains texts concerning Latin phonology, etymology, flexion and derivation, and lexical semantics, both with respect to individual words and to entire word classes. Both diachronic and synchronic perspectives are employed in the discussion of the various issues. The second volume ("Clause and Discourse") includes papers dealing with issues of syntax and semantics, and with the structure of texts and pragmatic aspects. One of the subchapters, entitled "Conversation and Dialogue", contains papers presented at the conference in a separate workshop of the same name, linked by a common methodological framework of "Conversation Analysis". This book provides essential texts for researchers in the field of Latin linguistics and may also be of use to linguists who work primarily with other languages